Sentiment and sociability - Mullan, John (Clarendon, 1988)
The rise of the novel in the mid-18th century was also the rise of sentimentalism. This study explores the attitudes which led novelists to associate virtuous feeling with disabling suffering. It also examines the role of women in fiction and in society during that period.
10.1093/acprof:oso/9780198122524.001.0001
Keywords: English literature; Sentimentalism in literature; Literature and society